Polysaccharides Obtained from Vegetables: an effective source of alternative excipient - Ananta Choudhury; Satyabrat Sarma; Snehashis Sarkar; Madhusmita Kumari; Biplab Kumar Dey (Korean Pharmacopuncture Institute, 2022)
Polymers are the major constructive material of pharmaceutical formulations that play a prime role in designing effective drug-delivery systems and releasing drugs at their sites of application. Polymers are composed of multiple repeating units of high molecular mass components with attendant properties. Most synthetic polymers are non-biocompatible, expensive, and extremely inclined to deliver adverse impacts. Meanwhile, edible polymers obtained from natural sources have gained remarkable recognition for their promising use in modern medicine. Moreover, polymers derived from natural sources are generally preferred due to certain of their unique features such as abundant availability, biocompatibility, nontoxicity, economical, safe, and effective functions that fit the purpose. Polysaccharides including starch, cellulose, hemicellulose, pectin, and mucilage are identified as a major class of naturally obtained molecules that have a substantial role as functional polymers. This review summarizes the potential role of polysaccharides derived from vegetable sources such as adhesives, anticaking agents, binders, disintegrants, emulsifiers, film-framing agents, and thickeners. This is simply an opportunity to abandon synthetic excipients that hurt our bodies and think back to nature from where we originate.